The take-action guide to world class learners, book 3 how to create a campus without borders - Zhao, Yong; Tavangar, Homa Sabet; McCarren, Emily; Rshaid, Gabriel F.; Tucker, Kay (Corwin, 2016)
Your blueprint for nurturing globally connected students The World Class Learners series provides the most complete information available on designing twenty-first century schools poised to leapfrog into the future! These practice-oriented books expand on Dr. Yong Zhao's acclaimed World Class Learners, which presents a new framework for cultivating creative and entrepreneurial students. Now, with this third book in the follow-up three-volume set, Zhao reveals how to help students learn and prepare for a globalized world. The third book in the series outlines how to: Transform students into strong, responsible global citizens Leverage experts, networks, and partner school relationships Implement a glocalized Global Campus or classroom Implement Zhao's new paradigm shift one phase at a time, starting with any book. Better yet, read all three volumes for a complete blueprint to entrepreneur-minded schooling. The ideal school should provide opportunities and resources to enable students to personalize their educational experiences instead of receiving a uniform standardized, externally prescribed, education diet. --Yong Zhao
Keywords: International education; Education and globalization